(untitled) (Journal of Applied Membrane Science & Technology, 2023)
For many different applications, functional polymeric materials are extremely important in electrochemical reactions. The development of polymer electrolytes, such as those used in fuel cells, depends heavily on these functional materials. One of the most significant sources of power for applications in numerous industries is provided by fuel cells. In this study, a proton exchange membrane (PEM) was developed using ethylene tetrafluoroethylene (ETFE) film with binary blends of acrylic acid (AA) and sodium styrene sulfonate (SSS), while NaCl served as an additive. As the monomer concentration increased, the degree of grafting (DG) increased. Gravimetric analyses, Fourier Transform Infrared (FTIR) spectroscopy, mechanical characteristics, and surface morphology (SEM) have all supported the radiation grafting. The physical and chemical durability of 60% DG of ETFE-g-AA-SSS film made it an ideal PEM for this study since it is more durable than other grafted samples of ETFE-g-AA-SSS film. The 60% DG of PEM’s ion-exchange capacity (IEC) was determined to be 0.26 mmol g-1. They demonstrated excellent thermal, mechanical, and acid stability characteristics. In H2O2 solutions, they are highly stable, and they display significant water uptake. It is therefore applicable to acidic fuel cells.